(untitled) (Revista Innova Educación, 2022)
The objective was to determine the effect of an educational intervention on the level of oral health knowledge in primary school teachers in the district of Huayrapata - Puno, Peru. Methodology: The research approach was mixed, the pre-experimental, longitudinal, and prospective designs. The sample consisted of 32 teachers from eight educational institutions selected as non-probabilistic for convenience considering the sample selection criteria. The study was carried out in three periods. First, a questionnaire of 18 questions was applied to teachers to determine the level of knowledge about preventive measures, main oral diseases, and dental development. Subsequently, the educational intervention was carried out, which consisted of didactic training with images and videos for teachers. Finally, the teachers were evaluated with the same 18-question questionnaire. The levels of knowledge were evaluated with a Likert scale as good, regular, and bad. The Wilcoxon non-parametric statistical test of ranks was used to test the hypothesis. Results: the results obtained before the educational intervention on the level of knowledge of oral health were good 28.12%, regular 65.6%, and bad 6.26%. After the educational intervention, the results obtained were a good level of knowledge 87.5%, regular 12.5%, and bad 0%. Conclusion: The educational intervention on the level of knowledge of oral health applied to the teachers of the district of Huayrapata - Puno, Peru was effective because their knowledge increased, which will have repercussions on their students and family.